Identification of circular RNAs and their altered expression under poly(I:C) challenge in key antiviral immune pathways in amphioxus. Issue 86 (March 2019) - Zhang, Qi-Lin; Ji, Xin-Yu; Li, Hong-Wei; Guo, Jun; Wang, Feng; Deng, Xian-Yu; Chen, Jun-Yuan; Lin, Lian-Bing
Abstract: Amphioxus is a key model for studying comparative immunity of vertebrates. Circular RNA (circRNA), as RNAs with a circular structure, has received little attention until recently, where several studies have reported that circRNA expression changes are involved in the immune response in animals. However, circRNA and its immune role in amphioxus have not been previously studied. Here, circRNAs in Chinese amphioxus ( Branchiostoma belcheri ) were sequenced, and 1859 circRNAs were identified using two algorithms (find_circ and CIRI). The analysis of miRNA target sites on circRNAs showed that 332 circRNAs may function as miRNA sponges. Furthermore, we identified circRNAs that were conserved between B. belcheri and vertebrates, tracing the origin of these circRNAs within chordates. Additionally, in combination with several key antiviral immune (poly(I:C), pIC) pathways identified in our previous B. belcheri studies, nine circRNAs potentially involved in these pathways were identified using bioinformatic predictions. Among these nine circRNAs, eight were selected to examine their expression response in B. belcheri challenged by pIC in comparison to control using real-time quantitative PCR. The results showed that four circRNAs were induced as part of the antiviral response against pIC, while expression of two circRNAs was decreased, and the expression levels of the remaining two were not significantly altered after pIC challenge. This work is the first to identify circRNAs and reveal their antiviral role in amphioxus. Therefore, it opens a new window to explore the comparative immunology of circRNAs in chordates and the regulatory roles of circRNAs in antiviral immunity in amphioxus. Highlights: 1859 circRNAs were identified in adult Branchiostoma belcheri. 332 circRNAs are identified potentially as miRNA sponges. Six circRNAs showed a gene expression alteration in response to pIC challenge. This is the first time to identify circRNAs and investigate their immune response in amphioxus.